Pallidal deep brain stimulation for DYT6 dystonia. Issue 2 (23rd September 2011) - Panov, Fedor; Tagliati, Michele; Ozelius, Laurie J; Fuchs, Tania; Gologorsky, Yakov; Cheung, Tyler; Avshalumov, Marat; Bressman, Susan B; Saunders-Pullman, Rachel; Weisz, Donald; Alterman, Ron L
Abstract : Background: Mutations of the THAP1 gene were recently shown to underlie DYT6 torsion dystonia. Little is known about the response of this dystonia subtype to deep brain stimulation (DBS) at the internal globus pallidus (GPi). Methods: Retrospective analysis of the medical records of three DYT6 patients who underwent pallidal DBS by one surgical team. The Burke–Fahn–Marsden Dystonia Rating scale served as the primary outcome measure. Comparison is made to 23 patients with DYT1 dystonia also treated with GPi-DBS by the same team. Results: In contrast with the DYT1 patients who exhibited a robust and sustained clinical response to DBS, the DYT6 patients exhibited more modest gains during the first 2 years of therapy, and some symptom regression between years 2 and 3 despite adjustments to the stimulation parameters and repositioning of one stimulating lead. Microelectrode recordings made during the DBS procedures demonstrated no differences in the firing patterns of GPi neurons from DYT1 and DYT6 patients. Discussion: Discovery of the genetic mutations responsible for the DYT6 phenotype allows for screening and analysis of a new homogeneous group of dystonia patients. DYT6 patients appear to respond less robustly to GPi-DBS than their DYT1 counterparts, most likely reflecting differences in the underlying pathophysiology of these distinct genetic disorders. Conclusions: While early results of pallidal DBS for DYT6 dystonia are encouraging, further research and additional subjects are needed both to optimise stimulation parameters for this population and to elucidate more accurately their response to surgical treatment.